THE APPLICATION OF THEORY OF PLANNED BEHAVIOR IN SINGLE-USE PLASTIC BAGS CONSUMPTION: A MEDIATING EFFECT OF ENVIRONMENTAL CONCERN - Vina, Delia
It’s estimated that a total of 9.85 billion plastic bags are generated every year for the supermarkets in Indonesia, which brings challenges as it could harm both the environment and humans. Moreover, the awareness of plastic bags and managing plastic waste is still very low in Indonesia. Several efforts have been made to reduce the use of plastic bags; however, many people still use plastic bags at the supermarket. Thus, this research analyzes the drivers of the behavior to reduce the use of plastic bags among 386 consumers in Bandung with the use of the extended theory of planned behavior (TPB), by adding environmental concern. The research was conducted using questionnaires and analyzed using Partial Least Square (PLS) – SEM method, with SmartPLS Software. The results indicate that consumers’ subjective norm, perceived behavioral control, and environmental concern positively and significantly influence the intention to reduce the use of plastic bags, except for attitudes that have positive but not significant effects. Furthermore, environmental concern positively and significantly affects the consumers’ attitude, subjective norms, perceived behavioral control, and intention to reduce the use of plastic bags. While consumers’ perceived behavioral control and intention to reduce the use of plastic bags positively and significantly affect the behavior to reduce the use of plastic bags. The attitude, subjective norm, and perceived behavioral control partially mediate the effect of environmental concern on the intention to reduce the use of plastic bags. The effect of environmental concern on the behavior to reduce the use of plastic bags is fully mediated by perceived behavioral control, partially mediated by the intention to reduce the use of plastic bags, and partly mediated by the combination of attitude, subjective norms, and perceived behavioral control with intention. These findings might be useful to create strategies to reduce the single-use plastic bags consumption in Indonesia, by focusing on increasing consumer’s environmental concern, subjective norms, and perceived behavioral control.